1991
DOI: 10.1080/15287399109531513
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of quartz and chrysotile asbestos: In vitro interspecies comparison with alveolar macrophages

Abstract: Cytotoxic effects of DQ12 quartz and chrysotile asbestos on alveolar macrophages of different animal species were compared in vitro. The type of cell reaction toward the cytotoxic dusts was always the same: a loss of cell viability (trypan blue dye exclusion test) was accompanied by the release of cytoplasmic and lysosomal enzymes. The extent of cellular destruction depended upon the amount of dust applied. In the range of 50-100 micrograms/ml quartz or chrysotile asbestos, species-specific variations were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Several studies showed that fibers with a high aspect ratio generate reactive oxygen species (ROS), stimulate tumor necrosis factor (TNF) α release, and stimulate inflammatory transcription factor NF-κB activation (Brown et al, 2007;Dogra & Donaldson, 1995;Hill et al, 1995). MWCNT were also found to resemble asbestos fibers in that MWCNT fibers interfered with the ability of macrophages to produce phagocytosis (Soto et al, 2004;Manning et al, 2002;Schimmelpfeng & Seidel, 1991).…”
mentioning
confidence: 97%
“…Several studies showed that fibers with a high aspect ratio generate reactive oxygen species (ROS), stimulate tumor necrosis factor (TNF) α release, and stimulate inflammatory transcription factor NF-κB activation (Brown et al, 2007;Dogra & Donaldson, 1995;Hill et al, 1995). MWCNT were also found to resemble asbestos fibers in that MWCNT fibers interfered with the ability of macrophages to produce phagocytosis (Soto et al, 2004;Manning et al, 2002;Schimmelpfeng & Seidel, 1991).…”
mentioning
confidence: 97%
“…Silica-induced lung injury is an established murine model of pulmonary fibrosis [7,33]. A single dose of the highly toxic DQ12 silica [7,34,35] induced a severe and persistent alveolitis characterized by significant increases in lactate dehydrogenase (LDH) and total protein content in BAL fluid. Concomitantly, a rapid and significant recruitment of monocytes/macrophages and neutrophils was also noted in response to silica (table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The NE cell hyperplasia in the rat-the species of choice for silica carcinogenesis-and its possible role in stimulating cell proliferation in the adjacent epithelia represents a further hypothetical mechanism. These species differences may be related to other differences in the inflammatory cell response to silica (Driscoll et al, 1996;Schimmelpfeng and Seidel, 1991) and to the role of growth factors such as TGF-␤ and TNF-␣ (Saffiotti, 1993;Williams et al, 1996).…”
Section: Discussionmentioning
confidence: 99%